2016
DOI: 10.4028/www.scientific.net/msf.841.98
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Geopolymer Based on the Fly Ash Variation

Abstract: . This study was conducted to determine the factors that may affect the compressive strength of fly ash-based geopolyme, manufactured using fly ash obtained from different power plants. Fly ash obtained from different sources may have very different characteristics that affect the properties of geopolymer product. The source of variations in the geopolymer properties from the view point of the source materials can be classified into internal and external factors. Internal factors include the physical and chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Research conducted by Antoni revealed that pH value of fly ash influence the setting time of geopolymer paste [11]. The pH value was tested by dissolving fly ash into distilled water followed with pH measurement.…”
Section: Ph Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Antoni revealed that pH value of fly ash influence the setting time of geopolymer paste [11]. The pH value was tested by dissolving fly ash into distilled water followed with pH measurement.…”
Section: Ph Testmentioning
confidence: 99%
“…Research conducted by Antoni stated that degree of acid or pH from fly ash plays an important role in setting time of geopolymer paste. Higher pH level of fly ash induces faster setting time of geopolymer paste [10,11]. XRD test was performed in order to discover crystalline mineral component of fly ash [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fly ash samples for making geopolymer were obtained from a power plant located in Paiton, East Java, Indonesia. It was reported as a good precursor for making good geopolymer [10]. A combination of chemical grade sodium hydroxide (NaOH) and sodium silicate solution was used as the alkaline activator.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The authors' previous studies [9,10] have found that fly ash obtained from different power plants in Java island, Indonesia, produced different properties of the resulting geopolymer mortar. Setting time and compressive strength are affected by the physical and chemical properties of the fly ash used.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally CaO content in the mixture also affect the value of setting time. Fly ash has higher a CaO content compared to metakaolin so that a mixture that containing a lot of metakaolin will have fewer CaO content that deliver long setting time [13].…”
Section: Compressive Strengthmentioning
confidence: 99%